Medical Students “The Night Owls”: Cross-Sectional Analysis of the Sleep Habits of Medical Undergraduates of an Institute in Northern India - Navneet Kumar Kaushik; Anju Sharma (Journal of Sleep Sciences)
Background and Objective: Sleep is a biological necessity and essential for optimal health. Literature suggests college students are an at-risk population for sleep deprivation; hence, the present research was undertaken to assess the sleep habits of medical student population.